Islamization of Science in The Digital Era: Challenges and Opportunities in the Integration of Science and Islamic Values - Ria, Andi Sitti Emeralda; Yahdi, Muhammad (Golden Ratio of Data in Summary, 2025)
This study explores the complex dynamics of Islamization of science in the digital era, focusing on the challenges and opportunities involved in integrating Islamic values into contemporary scientific paradigms. Employing a descriptive quantitative design, the research surveyed 350 Muslim academics and students across Islamic universities in Southeast Asia and the Middle East. The findings reveal widespread awareness of Islamization, yet significant variations in conceptual understanding across disciplines and age groups. Challenges include epistemological tensions with secular science, institutional limitations, and technological infrastructure gaps. Conversely, digital tools—such as e-learning platforms, AI-based content, and augmented reality—emerge as transformative instruments for disseminating Islamic scientific perspectives. Respondents called for strategic policy support, interdisciplinary centers of excellence, and transnational collaboration to sustain these efforts. The study highlights the importance of nurturing a generation of Muslim scholars capable of bridging scientific knowledge with spiritual wisdom, thereby offering a holistic framework for scientific inquiry rooted in tawhid and ethical accountability. The results contribute empirically to the growing discourse on Islamization and offer actionable recommendations for educational institutions, policymakers, and scholars engaging with Islamic epistemology in modern science.